2007
DOI: 10.1186/1471-244x-7-63
|View full text |Cite
|
Sign up to set email alerts
|

Auditory target processing in methadone substituted opiate addicts: The effect of nicotine in controls

Abstract: Background: The P300 component of the auditory evoked potential is an indicator of attention dependent target processing. Only a few studies have assessed cognitive function in substituted opiate addicts by means of evoked potential recordings. In addition, P300 data suggest that chronic nicotine use reduces P300 amplitudes. While nicotine and opiate effects combine in addicted subjects, here we investigated the P300 component of the auditory event related potential in methadone substituted opiate addicts with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…This implies, that a paradigm or task is employed that can robustly elicit certain brain regions or more integrated functional circuits [e.g. [60][61][62]64]. Such paradigms can be cognitive tasks, but also more passive conditions such as the oddball paradigm [e.g.…”
Section: Fmri To Study Acute Pharmacological Effectsmentioning
confidence: 99%
“…This implies, that a paradigm or task is employed that can robustly elicit certain brain regions or more integrated functional circuits [e.g. [60][61][62]64]. Such paradigms can be cognitive tasks, but also more passive conditions such as the oddball paradigm [e.g.…”
Section: Fmri To Study Acute Pharmacological Effectsmentioning
confidence: 99%
“…Because it has been shown that nicotine can also affect the CNS of humans, in a novel study Muller et al () investigated the effect of nicotine on the P300 component among MMT subjects and found a decline in P300 amplitude among nicotine dependents (Muller et al, ). It was also suggested that target attentional processing disability can be reorganized for MMT subjects; however, a significant result of this study showed that the effects of nicotine on P300 amplitude among healthy subjects exceeds the effects of MMT on heroin dependents.…”
Section: Brain Electrophysiological Findingsmentioning
confidence: 99%
“…ERPs consist of time-locked components related to information processing operations that provide a reliable approach for studying brain-behavior relations, information processing, and cognitive biases (Boutros et al, 1997;Handy, 2005). Standard ERP investigations include three types of paradigms (Table II): 1) oddball paradigms (standard and target stimuli) during resting conditions (Bauer, 2001;Kivisaari et al, 2007;Muller et al, 2007;Singh et al, 2009) or during the exposure of various emotional targeting slides (Marques-Teixeira and Barbosa, 2005), 2) visual Go-No Go paradigms that use neutral or emotional conditions (Yang et al, 2009;Morie et al, 2014), and 3) the standard digit span Wechsler test paradigm (Papageorgiou et al, 2001(Papageorgiou et al, , 2003(Papageorgiou et al, , 2004Kalatzis et al, 2005).…”
Section: Standard Erp Paradigmsmentioning
confidence: 99%
“…Some studies reported changes in P300 amplitude and latency in cases of chronic consumption of nicotine, alcohol, as well as cannabis, opioids, cocaine, and ecstasy (Table 2) (8,(54)(55)(56)(57)(58)(59)(60).…”
Section: Review Of Literaturementioning
confidence: 99%
“…ERP components such as auditory evoked P300, associated with cognitive processes (i.e., attention and orientation), show low amplitude and long latency in acute and chronic diseases (4)(5)(6). P300 testing is an unbiased and non-invasive method, standardized for assessing cognitive processes (7)(8)(9)(10). We have reviewed the existing literature in this field to better understand the role of P300 testing in diagnostics of different diseases.…”
Section: Introductionmentioning
confidence: 99%